Birds of Malagos Watershed: A Comparative Sourvey - Alviola, Geonsyl L.; Otadoy, Julie B.; del Rosario, Bernadette I.; Ibañez, Jason (JPAIR Multidisciplinary Research, 2008)
The study titled "Birds of Malagos Watershed, Southeastern Philippines" highlights the avifaunal richness of Mindanao, one of the most biodiverse islands in the Philippines. Conducted in Malagos watershed, Baguio District, Davao City, the study aimed to identify and classify bird species, assess their distribution, and compare taxonomic listings with previous avian surveys. Using point count and mist netting methods, 54 bird species from 27 families were identified, including three new families not recorded in earlier studies. Among these were 12 Philippine endemic species, seven Mindanao endemic species, 32 resident species, and four species classified as vulnerable or endangered. The findings indicate that the area is disturbed, as most birds observed were associated with open and cultivated habitats. A comparative analysis with three previous surveys revealed a steady increase in bird population from 1994 to 2002 but noted a decline in species diversity in the current study. This negative trend is attributed to habitat destruction and anthropogenic activities. The study underscores the importance of conservation efforts to mitigate threats to biodiversity and protect vulnerable bird populations.